Carry-Over Effects Modulated by Salinity During the Early Ontogeny of the Euryhaline Crab Hemigrapsus Crenulatus from the Southeastern Pacific Coast: Development Time and Carbon and Energy Content of Offspring - Guzman-Rivas, F (Elsevier Inc., 2018)
Hemigrapsus crenulatus is a key species of coastal and estuarine ecosystems in the Southeastern Pacific and New Zealand. Since the gravid females-and their embryos-develop under conditions of variable salinity, we propose that low external salinity will be met with an increase in energy expenditures in order to maintain osmoregulation; subsequently, the use of energy reserves for reproduction will be affected. In this study, we investigate in H. crenulatus whether 1) the biomass and energy content of embryos is influenced by salinity experienced during oogenesis and embryogenesis and 2) how variation in the biomass and energy content of embryos affects larval energetic condition at hatching. Here at low salinity (5 PSU), egg-bearing females experienced massive and frequent egg losses, and therefore the development of their eggs during embryogenesis was not completed. In turn, at intermediate and high salinity (15 and 30 PSU) embryogenesis was completed, egg development was successful, and larvae were obtained. Consistently, larvae hatched from eggs produced and incubated at high salinity (30 PSU) were larger, had higher dry weight, and had increased carbon content and energy than larvae hatched from eggs produced at intermediate salinity (15 PSU). From these results, it is seen that the size and biomass of early life stages of H. crenulatus can be affected by environmental salinity experienced during oogenesis and embryogenesis, and this variation can then directly affect the energetic condition of offspring at birth. Therefore, this study reveals a “cascade effect” modulated by salinity during the early ontogeny. © 2018 Elsevier Inc.